AB0573 The immunogenicity of biological therapies correlates with clinical efficacy in psoriatic arthritis (psa) in long-term treatment with infliximab and adalimumab. (23rd January 2014) - Cajigas, D.; Plasencia, C.; Pascual-Salcedo, D.; Bonilla, G.; Alcocer, P.; García-Carazo, S.; Franco, K. N.; Lojo, L.; Nuño, L.; Villalba, A.; Peiteado, D.; Ramiro, S.; et al.
Abstract : Background: In psoriatic arthritis (PsA) with peripheral involvement classical DMARDs refractory, the anti-TNF therapy has proven to be effective. In recent years, there are some publications that demostrate the correlation between clinical activity and the anti-drug antibodies (ADA) development in rheumatic diseases such as rheumatoid arthritis (RA) and spondyloarthritis (SpA). To date, there is no studies that reveals theses findings in PsA patients treated with infliximab (Ifx) and adalimumab (Ada). Objectives: To evaluate in PsA patients treated with Ifx and Ada wether the development of ADA correlate with clinical activity and biological treatment discontinuation. Methods: We studied 37 patients with PsA treated with Ifx and Ada from La Paz University Hospital. Clinical activity was assessed using the Disease Activity Score 28 (DAS28), clinical improvement by the delta-DAS28 and treatment response by EULAR criteria at baseline, at 6 months, at 1 year and at > 2nd years of treatment. Ifx and Ada were administred at standard therapeutic schedule. Serum drug and ADA levels were measured by ELISA. Statistical analysis was performed using SPSS 11.0. Results: Of the total of patients, 24/37 (64.9%) were treated with Ifx and 13/37 (35.1%) with Ada, being female 23 (62.1%). The mean age was 55.1 ± 12.3 years and the mean disease duration was 14.4 ± 9.9 years. The average time on biological therapy was 4.4 ± 3.2 years. Most patients received concomitantly classical DMARDs [29/37 (78.3%) with DMARDs vs 8/37 (21.7%) in monotherapy]. At baseline, clinical activity (DAS28) was higher in patients who subsequently not developed ADA (5.1 ± 0.9 without ADA vs 13.4 ± 0.6 with ADA, p = 0.021). Clinical activity (DAS28) tended to be higher in patients with ADA at all studied time points (5.4 ± 1.2 with ADA vs 2.8 ± 1.3 without ADA at 6 months, p = 0.007; 4.0 ± 1.2 with ADA vs 3.0 ± 1.3 without ADA at 1 year, p = 0.144; 2.9 ± 1.3 with ADA vs 2.4 ± 0.4 without ADA a> 2nd year, p = 0.169). Clinical improvement (delta-DAS28) was lower in patients with ADA throughout the study (-1.0 ± 1.6 with ADA vs 2.0 ± 1.4 without ADA at 6 months, p = 0.006, 0.3 ± 1.8 with ADA vs 2.1 ± 1.5 without ADA at 1 year, p = 0.052; 0.9 ± 1.5 with ADA vs 2.7 ± 0.8 without ADA a> 2nd year, p = 0.007). Patients without ADA were classified as responders more frequently based on criteria EULAR [2/5 (40%) with ADA vs. 27/30 (90%) without ADA, p = 0.006]. The median time to drug discontinuation was lower in patients with ADA (4.83 ± 1.6 years with ADA vs 7.93 ± 1.4 years without ADA, p = 0.061). The dose increase was more frequent in patients with ADA [3/6 (50%) with ADA vs 4/31 (12.9%) without ADA, p = 0.053], and in contrast, in patients without ADA was more often performed dose decrease of anti-TNF therapy [0/6 (0%) with ADA vs 15/31 (48.3%) without ADA, p = 0.053]. Conclusions: The development of ADA correlates with poorer clinical response and more frequent treatment discontinuation in PsA patients in long-term treatment with Ifx and Ada. Disclosure of Interest: None Declared